The end-expiratory occlusion test for detecting preload responsiveness: a systematic review and meta-analysis - Gavelli, Francesco (Ann Intensive Care, 2020)
BACKGROUND: We performed a systematic review and meta-analysis of studies assessing the end-expiratory occlusion test (EEXPO test)-induced changes in cardiac output (CO) measured by any haemodynamic monitoring device, as indicators of preload responsiveness. METHODS: MEDLINE, EMBASE and Cochrane Database were screened for original articles. Bivariate random-effects meta-analysis determined the Area under the Summary Receiver Operating Characteristic (AUSROC) curve of EEXPO test-induced changes in CO to detect preload responsiveness, as well as pooled sensitivity and specificity and the best diagnostic threshold. RESULTS: Thirteen studies (530 patients) were included. Nine studies were performed in the intensive care unit and four in the operating room. The pooled sensitivity and the pooled specificity for the EEXPO test-induced changes in CO were 0.85 [0.77–0.91] and 0.88 [0.83–0.91], respectively. The AUSROC curve was 0.91 [0.86–0.94] with the best threshold of CO increase at 5.1 ± 0.2%. The accuracy of the test was not different when changes in CO were monitored through pulse contour analysis compared to other methods (AUSROC: 0.93 [0.91–0.95] vs. 0.87 [0.82–0.96], respectively, p = 0.62). Also, it was not different in studies in which the tidal volume was ≤ 7 mL/kg compared to the remaining ones (AUSROC: 0.96 [0.92–0.97] vs. 0.89 [0.82–0.95] respectively, p = 0.44). Subgroup analyses identified one possible source of heterogeneity. CONCLUSIONS: EEXPO test-induced changes in CO reliably detect preload responsiveness. The diagnostic performance is not influenced by the method used to track the EEXPO test-induced changes in CO. Trial registration The study protocol was prospectively registered on PROSPERO: CRD42019138265.